Association between family history of suicide attempt and neurocognitive functioning in community youth. (30th March 2020) - Jones, Jason D.; Boyd, Rhonda C.; Calkins, Monica E.; Moore, Tyler M.; Ahmed, Annisa; Barzilay, Ran; Benton, Tami D.; Gur, Raquel E.; Gur, Ruben C.
Abstract : Background: Suicidal behavior is highly familial. Neurocognitive deficits have been proposed as an endophenotype for suicide risk that may contribute to the familial transmission of suicide. Yet, there is a lack of research on the neurocognitive functioning of first‐degree biological relatives of suicide attempters. The aim of the present study is to conduct the largest investigation to date of neurocognitive functioning in community youth with a family history of a fatal or nonfatal suicide attempt (FH). Methods: Participants aged 8–21 years from the Philadelphia Neurodevelopmental Cohort completed detailed clinical and neurocognitive evaluations. A subsample of 501 participants with a FH was matched to a comparison group of 3, 006 participants without a family history of suicide attempt (no‐FH) on age, sex, race, and lifetime depression. Results: After adjusting for multiple comparisons and including relevant clinical and demographic covariates, youth with a FH had significantly lower executive function factor scores ( F [1, 3432] = 6.63, p = .010) and performed worse on individual tests of attention ( F [1, 3382] = 7.08, p = .008) and language reasoning ( F [1, 3387] = 5.12, p = .024) than no‐FH youth. Conclusions: Youth with a FH show small differences in executive function, attention, and language reasoning compared to youth without a FH. Further research is warranted to investigate neurocognitive functioning as an endophenotype for suicide risk. Implications for the prevention and treatment of suicidal behaviors are discussed.